Implementing Video-Based Online Learning in an Asynchronous Setting: A Case Study at Madrasah Aliyah - Mundir Mundir (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to understand the implementation of video-based online learning with an asynchronous platform during the Covid-19 pandemic at Madrasah Aliyah Negeri (MAN) in Jember. This research is based on a qualitative case study approach. The data collection technique is done through observation, interviews and documentation. Data analysis is done through data collection is done through virtual interview techniques, non-participant observation, and documentation. Meanwhile, data analysis was carried out using the interactive model of Miles and Hubermann. The results showed that; 1) The design of video-based asynchronous online learning is based on the synergy between the school's internal curriculum as stated in the education policy determined by the head of the institution; the use of learning technology, as well as the teacher's pedagogical aspects which are reflected in the design of planning, implementation, and evaluation of learning; 2) The implementation of video-based asynchronous online learning is implemented through the use of "classroom" and "e-learning". This study implies the importance of online learning, which must be designed in such a way by utilizing various learning resources by practitioners and managers of educational institutions in order to create effective and efficient student-centred learning by utilizing information and technology developments.